The technological economy - Barry, Andrew, 1960-; Slater, Don (Routledge, 2005)
In this major new collection, leading experts explore the multidisciplinary connections between technology and economy, drawing on new convergences between economic sociology and science and technology studies. Through theoretical and empirical studies, the authors investigate:* economics and economic knowledges as technologies* the economies as socio-technical arrangements* the nature of innovation* the role of technological mediations in representing and performing economies. This revealing book, ideal for those with an interest in contemporary social theory, interrogates the evidence for th.